The Importance of Parenting for a Generation of Well-Mannered Children: Empowering Parents Through Parenting Socialization - Jariyah, Ita Ainun; Adam, Jauhar Isbamami (Jurnal Pengabdian Nusantara, 2025)
Normative behavior is a behavior that is in accordance with the norms that surround them. Normative behavior is often interpreted as ethics, where an ethic is often also associated with morals. This article aims to outline the devotion of the importance of parenting to parents so that children's behavior does not deviate from existing morals and norms. Community service "The Importance of Parenting for a Generation of Well-mannered Children: Empowering Parents Through Parenting Socialization" is done through socialization. Based on the results of interviews with parents of students, several results were obtained after participating in socialization activities and applying techniques regarding behavior modification that had been taught, where there were positive changes in children's behavior. Through an effective parenting program, it can significantly change how children behave in accordance with the norms. Based on the discussion above, it can be concluded that in the service program that has been carried out regarding parenting programs has had a positive impact on parents where they better understand the importance of effective parenting in supporting normative behavior in children, so that children behave in accordance with existing norms such as not disobeying parental rules, being more manageable, and not saying harsh words.